Pengaruh Jadwal Irigasi Terhadap Pemakaian Air Konsumtif dan Produksi Nilam (Pogostemon cablin (Blanco) Benth) - Sulistyono, Eko; Yanuar, Sandi (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2008)
The objective of this research was to study the effect of irrigation schedule on consumptive water use and yield of patchouli. The irrigation schedule treatment was combination between irrigation level and growth phase. Irrigation levels included irrigation until field capacity were applied every day (100% Available Water/AW1), 3 days (100% AW3), 6 days (100% AW6), 9 days (100% AW9), irrigation until 75% of available water every day (75% AW1), 50% of available water every day (50% AW1) and 25% of available water every day (25% AW1). The growth phase was described into whole growth phase, 2 weeks before harvest and 4 weeks before harvest. Results showed that consumptive water-use ranged from 129.18 cm/4 months to 47.58 cm/4 months that was equivalent to 63379 l water in pot with 25 cm diameter (100% AW3 applied at 4 weeks before harvest) to 23344 l water in pot with 25 cm diameter (25% AW1 applied during whole growth phase), respectively. High water use efficiency was yielded by irrigation level of 50% AW1 or 100% AW6. High productivity was reached by irrigation level of 50% AW1 or 100% AW3. Key words: Irrigation schedule, water use efficiency, available water, Pogostemon cablin